Low-Cost Sensors Based on Nanoparticles of Tin Dioxide Decorated with Graphene Used to Detect Ultra-Low NO2 Concentrations at Room Temperature - Isabel Sayago; Carlos Sánchez-Vicente; José Pedro Santos (Proceedings)
Chemical nanosensors based on nanoparticles (NPs) of pure tin dioxide (SnO2) and graphene-decorated tin dioxide were developed and characterized for the detection of pollutant gases. Sensitive layers were prepared by a drop casting method. The photoactivation of the sensors allows for the detection of ultra-low NO2 concentrations (50 ppb) at room temperature. The sensors show strong responses to NO2 and weak ones to the other tested polluting gases (CO, CH4 and CO2). The effect of humidity and the presence of graphene on the sensors’ response were studied.